Poxvirus pathology and pathogenesis in agriculturally important species - MacNeill, Amy L.; Micheloud, Juan Francisco; Parvin, Rokshana; Gjessing, Mona; Airas, Niina A.; Sant’Ana, Fabiano José Ferreira de; Adamek, Mikolaj (Sage Publishing, 2025)
Zoonotic poxviruses, including monkeypox virus (MPV), the causative agent for Mpox disease, have gained significant media and scientific attention due to recent outbreaks in human populations across the globe. The increase in human cases of poxvirus infection is not unexpected, as routine vaccination against smallpox (a disease caused by the poxvirus variola virus, which cross protects against other orthopoxviruses) was discontinued in the 1980s after its eradication. Large numbers of vertebrate and invertebrate species are susceptible to infection by Poxviridae. Clinical signs and histologic lesions caused by genetically different poxviruses can be strikingly similar with some notable exceptions (eg, poxviral infections in fish). The purpose of this article is to review poxvirus pathology and pathogenesis observed in species of agricultural significance including poultry, cattle, goats, sheep, camels, swine, rabbits, horses, salmon, and carp.